Spontaneously-buckled microstructure of copper nanowire conductors for a highly stretchable heater. Issue 39 (17th September 2021) - Zhao, Le; Yu, Shihui; Li, Junjun; Song, Zichen; Wu, Muying; Wang, Xiuyu; Wang, Xiaohu
Abstract : The applications of stretchable conductors, which spontaneously form microbuckles on flexible substrates in micro and nano manufacturing, flexible and stretchable electronic technology, medicine, and other fields, have attracted extensive attention. Abstract : The applications of stretchable conductors, which spontaneously form microbuckles on flexible substrates in micro and nano manufacturing, flexible and stretchable electronic technology, medicine, and other fields, have attracted extensive attention. To demonstrate high-performance stretchable electrodes, a great deal of effort has been made in terms of high conductivity, high stretchable properties, and high durability. However, the application of stretchable electrodes remains challenging because the electrical conductivity degrades and is even lost when stretched due to induced mechanical tension and excessive deformation. This paper reports a highly stretchable and conductive electrode, fabricated using a polymer composite membrane (spun on the polymer substrate surface coated with a thin layer of Cu NWs and covered with a layer of chitosan), which is attached to the pre-draft elastomeric substrate and then releases the prestrain. The prepared electrode has excellent properties such as unchanged stretchable stability under 70% strain. In particular, the sheet resistance changes less than 13% at 175% strain and remains almost constant after 2500 stretchable cycles at the same strain. Finally, a stretchable heater based on the electrode was fabricated to verify the utility of the stretchable electrode, and the practicability of the stretchable conductor was confirmed through the circuit and human-wearable experiment.